Outcomes of complex decongestive therapy in managing upper limb lymphedema in female breast cancer patients at a palliative care unit of a tertiary care hospital in Bangladesh - Rifat Jahan; A.K.M. Motiur Rahman Bhuiyan; Afroja Alam; Mostofa Kamal Chowdhury; Romena Hassan; Nisha Mortuja Aktar (PLoS ONE, 2025)
Background Lymphedema is a chronic condition that significantly affects both physical function and quality of life of breast cancer patients. Although there is no definitive cure, various treatment options exist to alleviate its symptoms. Among these, Complex Decongestive Therapy (CDT) is widely regarded as a primary approach. This study seeks to evaluate the effectiveness of CDT for breast cancer patients with upper limb lymphedema and aims to assess the benefits of this treatment despite the challenges and constraints in resource-limited settings. Methods This observational study was conducted among 42 female breast cancer patients with unilateral upper limb lymphedema attending the Lymphedema Clinic of the Department of Palliative Medicine at Bangladesh Medical University in Dhaka, Bangladesh. Limb volume, skin condition, and clinical signs and symptoms were assessed at baseline. All patients received the intensive phase of Complex Decongestive Therapy (CDT) for 6 weeks, with follow-up assessments conducted at the 3rd week and the 6th week. Result A significant reduction in the volume of the affected limbs was observed from baseline to the 6th week, as well as from the 3rd week to the 6th week. Although no statistically significant improvement in skin edema was recorded during this period, visible clinical improvement in skin texture was noted. After receiving CDT and proper skin care, 59.5% of patients regained normal skin on the affected limb. Additionally, there was a significant reduction in self-reported symptoms such as tightness, heaviness, and pain in the affected limb from baseline to the 6th week. Conclusion Lymphedema management using all components of Complex Decongestive Therapy (CDT) was found to be effective in reducing limb volume and alleviating the distressing symptoms of patients. Timely referral of lymphedema patients to specialized clinics and initiation of CDT can significantly reduce their ongoing suffering in Bangladesh.